1991
DOI: 10.1016/0002-9343(91)80090-9
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol consumption—A risk factor for hemorrhagic and non-hemorrhagic stroke

Abstract: The results suggest that low levels of alcohol consumption may have some protective effect upon the cerebral vasculature, whereas heavy consumption predisposes to both hemorrhagic and non-hemorrhagic stroke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
1

Year Published

1996
1996
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(34 citation statements)
references
References 38 publications
0
33
0
1
Order By: Relevance
“…Not all seizures in patients experiencing alcohol withdrawal are alcohol withdrawal seizures. Approximately 50% of these seizures are a result of some other organic cause, such as repetitive brain trauma; thus, alcohol withdrawal seizure is still a diagnosis of exclusion (8,32). Other signs of alcohol withdrawal, namely, autonomic hyperactivity, may not be associated with these seizures, and in chronically alcoholdependent patients, the seizures may occur while the patient has blood alcohol levels that exceed the legal limit of intoxication (33)(34)(35).…”
Section: Diagnosis and Clinical Manifestationsmentioning
confidence: 99%
“…Not all seizures in patients experiencing alcohol withdrawal are alcohol withdrawal seizures. Approximately 50% of these seizures are a result of some other organic cause, such as repetitive brain trauma; thus, alcohol withdrawal seizure is still a diagnosis of exclusion (8,32). Other signs of alcohol withdrawal, namely, autonomic hyperactivity, may not be associated with these seizures, and in chronically alcoholdependent patients, the seizures may occur while the patient has blood alcohol levels that exceed the legal limit of intoxication (33)(34)(35).…”
Section: Diagnosis and Clinical Manifestationsmentioning
confidence: 99%
“…Excessive alcohol intake, especially binge drinking, has been associated with stroke [1][2][3][4][5], cardiac arrhythmias [6][7][8], sudden cardiac death [9,10], and cardiovascular mortality [11]. Furthermore, several studies have shown that excessive alcohol consumption is linked to higher prevalence of both hypertension [12][13][14][15] and target organ damage [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Die Hypothese einer protektiven Wirkung von Alkoholkonsum auf das Schlaganfallrisiko wird durch eine Reihe weiterer prospektiver Kohortenstudien [8,59,60,68,113] und Fallkontrollstudien [31,71,79,85] unterstützt, die im Einzelnen hier nicht weiter dargestellt werden sollen (Übersicht bei [13]). In Tabelle 2 sind die Eckdaten der größeren prospektiven Kohortenstudien zusammengefasst.…”
Section: Schützt Alkoholkonsum Vor Schlaganfall?unclassified